Kontribusi Motivasi Akademik Dosen Penasihat Akademik terhadap Prestasi Akademik Mahasiswa - Fuadi, Anwar; Rif'at, Muhammad; Ilham, Ilham; Rani, Samsul (Attractive : Innovative Education Journal, 2024)
Academic Advisor Lecturers (DPA) are lecturers assigned by the University to assist students in living their academic life on campus. Apart from being a lecturer, a DPA can also be a motivator for students' successful academic achievement, although in reality there are DPAs who actually become obstacles to students' academic progress. The research was conducted on Islamic Guidance and Counseling students at Antasari State Islamic University (UIN) Banjarmasin. The number of respondents studied was 286 active students majoring in BPI UIN Antasari Banjarmasin. The data analysis carried out was regression analysis using the SPSS v22.0 application. The hypothesis raised is that there is an influence of DPA as a builder of academic motivation and student achievement at BPI UIN Antasari Banjarmasin. Based on the research results, it can be concluded that an academic advisor lecturer is able to provide motivation to students who are studying at university. An advisor lecturer is able to become a motivation builder to make his students' achievements better in the future by 71.2%. Keywords: Academic Advisor Lecturer, Motivation, Student Achievement